Intermediate uveitis: Its relationship with multiple sclerosis and unique management considerations - Lopez, Sarah (Canadian Journal of Optometry, 2022)
This is a case report demonstrating the appropriate diagnosis and management of intermediate uveitis associated with multiple sclerosis. Though uveitis is not the most common ocular inflammatory sign in multiple sclerosis, a careful case history and evaluation should be conducted in patients with intermediate uveitis to rule out multiple sclerosis. This is especially important prior to the initiation of TNF-alpha inhibitors in cases of recalcitrant uveitis. Eye care providers must be aware of the steps taken to screen for multiple sclerosis in patients with intermediate uveitis and the appropriate management.